BASAMO SAMARINDA'S HERBAL AND HERBAL HEALTH BUSINESS IN THE MIDST OF THE PANDEMIC COVID-19 - Ilham Abu; Muhammad Sultan; Emil Riza Putra (Berkala Akuntansi dan Keuangan Indonesia, 2021)
The Covid-19 pandemic has had a broad impact on all sectors of life in Indonesia, including the economic sector. Not a few business sectors are experiencing losses and even bankruptcy. Therefore, business actors must be able to implement and develop certain strategies in order to survive and gain profits both in the midst of the pandemic storm and after the Covid-19 pandemic. This study aims to obtain information about the strategies of Herbal and Herbal Medicine business players in Sehat Basamo in the midst of the Covid-19 pandemic. This study uses a qualitative design with a case study approach. Research informants are sellers of herbs and herbal medicine Sehat Basamo as many as 4 people who were selected by purposive sampling. In addition, 4 informants were selected who are loyal customers at the Sehat Basamo outlet. The research was carried out in March-April 2021 at four locations of Sehat Basamo outlets in Samarinda City. The data and information obtained were then analyzed qualitatively. The results of the study obtained information that all Healthy Basamo herbal and herbal outlets and customers who visited Sehat Basamo outlets complied with the Covid-19 health protocol according to the government's appeal in controlling the spread of the Covid-19 rate. In addition to complying with health protocols, the Herbal and herbal medicine business of Sehat Basamo has also been proven to be able to survive in the midst of a pandemic and even continue to benefit from the sales of its products. The success of the owner of the Healthy Basamo herbal and herbal outlet in maintaining business continuity and still making profits in the midst of the Covid-19 pandemic by implementing a strategy that is consistent attitude in product presentation, not increasing product prices, friendliness and courtesy of sellers and ensuring the availability of product supply. Sales of herbal and herbal products from Sehat Basamo are carried out face-to-face with buyers and the financial accounting management is still manual. Therefore, sellers of Herbal and Jamu Sehat Basamo can take advantage of currently available technology and information both to increase product sales results and in managing digital-based business financial accounting (digital accounting) which is available in various application software.